Role of men in a women’s empowerment initiative: Evidence from Uganda - Ambler, Kate; Jones, Kelly M.; O'Sullivan, Michael (International Food Policy Research Institute, 2019)
Women’s empowerment is a significant element of economic development (Duflo 2012). Because most women in the developing world reside in male-headed households, considering the role of men in advancing women’s empowerment is an important research objective. In this note we report results related to the take-up of a women’s economic empowerment initiative aimed at sugarcane farmers in Uganda, and focus on the agency of men in determining the household’s participation. We also assess the impact of a couples-based workshop on project take-up. In this study, we partnered with Kakira Sugar Limited (KSL), a large sugar company near Jinja, Uganda, that sets the purchase price and buys most of its sugarcane from smallholder contract farm-ers, who are mainly men. Though women participate in labor related to sugarcane, they are infrequently involved in any of the sugar-related marketing activities, meaning that men generally control the sugar-related income.